Benefits of influenza vaccination on the associations between ambient air pollution and allergic respiratory diseases in children and adolescents: New insights from the Seven Northeastern Cities study in China. (January 2020) - Liu, Kangkang; Li, Shanshan; Qian, Zhengmin (Min); Dharmage, Shyamali C.; Bloom, Michael S.; Heinrich, Joachim; Jalaludin, Bin; Markevych, Iana; Morawska, Lidia; Knibbs, Luke D.; Hinyard, Leslie; Xian, Hong; et al.
Abstract: Background: Little information exists on interaction effects between air pollution and influenza vaccination on allergic respiratory diseases. We conducted a large population-based study to evaluate the interaction effects between influenza vaccination and long-term exposure to ambient air pollution on allergic respiratory diseases in children and adolescents. Methods: A cross-sectional study was investigated during 2012–2013 in 94 schools from Seven Northeastern Cities (SNEC) in China. Questionnaires surveys were obtained from 56 137 children and adolescents aged 2–17 years. Influenza vaccination was defined as receipt of the influenza vaccine. We estimated air pollutants exposure [nitrogen dioxide (NO2 ) and particulate matter with aerodynamic diameters ≤1 μm (PM1 ), ≤2.5 μm (PM2.5 ) and ≤10 μm (PM10 )] using machine learning methods. We employed two-level generalized linear mix effects model to examine interactive effects between influenza vaccination and air pollution exposure on allergic respiratory diseases (asthma, asthma-related symptoms and allergic rhinitis), after controlling for important covariates. Results: We found statistically significant interactions between influenza vaccination and air pollutants on allergic respiratory diseases and related symptoms (doctor-diagnosed asthma, current wheeze, wheeze, persistent phlegm and allergic rhinitis). The adjusted ORs for doctor-diagnosed asthma, current wheeze and allergic rhinitis among the unvaccinated group per interquartile range (IQR) increase in PM1 and PM2.5 were significantly higher than the corresponding ORs among the vaccinated group [For PM1, doctor-diagnosed asthma: OR: 1.89 (95%CI: 1.57–2.27) vs 1.65 (95%CI: 1.36–2.00); current wheeze: OR: 1.50 (95%CI: 1.22–1.85) vs 1.10 (95%CI: 0.89–1.37); allergic rhinitis: OR: 1.38 (95%CI: 1.15–1.66) vs 1.21 (95%CI: 1.00–1.46). For PM2.5, doctor-diagnosed asthma: OR: 1.81 (95%CI: 1.52–2.14) vs 1.57 (95%CI: 1.32–1.88); current wheeze: OR: 1.46 (95%CI: 1.21–1.76) vs 1.11 (95%CI: 0.91–1.35); allergic rhinitis: OR: 1.35 (95%CI: 1.14–1.60) vs 1.19 (95%CI: 1.00–1.42)]. The similar patterns were observed for wheeze and persistent phlegm. The corresponding p values for interactions were less than 0.05, respectively. We assessed the risks of PM1 -related and PM2.5 -related current wheeze were decreased by 26.67% (95%CI: 1.04%–45.66%) and 23.97% (95%CI: 0.21%–42.08%) respectively, which was attributable to influenza vaccination (both p for efficiency <0.05). Conclusions: Influenza vaccination may play an important role in mitigating the detrimental effects of long-term exposure to ambient air pollution on childhood allergic respiratory diseases. Policy targeted at increasing influenza vaccination may yield co-benefits in terms of reduced allergic respiratory diseases. Graphical abstract: Image 1 Highlights: Few studies on interaction between air pollution and influenza vaccine on asthma. A large population-based study to assess these interaction effects in China. Influenza vaccine may mitigate the detrimental effects of air pollution on asthma. Boys seem to be more sensitive to these interaction effects than girls.